Mnd1p: An evolutionarily conserved protein required for meiotic recombination - Gerton, Jennifer L. (The National Academy of Sciences, 2002)
We used a functional genomics approach to identify a gene required for meiotic recombination, YGL183c or MND1. MND1 was spliced in meiotic cells, extending the annotated YGL183c ORF N terminus by 45 aa. Saccharomyces cerevisiae mnd1–1 mutants, in which the majority of the MND1 coding sequence was removed, arrested before the first meiotic division with a phenotype reminiscent of dmc1 mutants. Physical and genetic analysis showed that these cells initiated recombination, but did not form heteroduplex DNA or double Holliday junctions, suggesting that Mnd1p is involved in strand invasion. Orthologs of MND1 were identified in protists, several yeasts, plants, and mammals, suggesting that its function has been conserved throughout evolution.